2011
DOI: 10.1007/s00535-011-0411-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of peginterferon alpha-2b and ribavirin following 24-week monotherapy of telaprevir in Japanese hepatitis C patients

Abstract: Anemia was manageable by carefully adjusting the ribavirin dosage in the standard therapy that followed telaprevir monotherapy. This sequential regimen seems to be safer and more tolerable than the triple combination of telaprevir, peginterferon alpha, and ribavirin, especially among elderly females with low baseline hemoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…One previous study indicated that mice infected with the resistant strain (A156F [99.9%]) developed only low-level viremia, and the virus was successfully eliminated with IFN therapy (27). In the other clinical report, telaprevir-resistant variants that emerged during 24-week telaprevir monotherapy were eliminated by the combination therapy of PEG-IFN plus ribavirin (28). Furthermore, this finding probably suggests that a small number of mutant-type viral RNAs may be incomplete or defective, since a large proportion of viral genomes are thought to be defective due to their high replication and mutation rates (29).…”
Section: Discussionmentioning
confidence: 99%
“…One previous study indicated that mice infected with the resistant strain (A156F [99.9%]) developed only low-level viremia, and the virus was successfully eliminated with IFN therapy (27). In the other clinical report, telaprevir-resistant variants that emerged during 24-week telaprevir monotherapy were eliminated by the combination therapy of PEG-IFN plus ribavirin (28). Furthermore, this finding probably suggests that a small number of mutant-type viral RNAs may be incomplete or defective, since a large proportion of viral genomes are thought to be defective due to their high replication and mutation rates (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, SVR was detected 24 weeks after combination therapy with PEG-IFN α-2b, ribavirin, and TVR. 4,17,30,31) Therefore, these results did not suggest SVR, but these might be steps to SVR.…”
Section: Discussionmentioning
confidence: 73%
“…26,27 Therefore, telaprevir must be administered as part of triple therapy with peginterferon and ribavirin to Emerging treatments for chronic HCV suppress viral breakthrough. Triple therapy consequently only increases the risk of adverse effects and imposes further restrictions on an already restrictive therapy.…”
Section: Telaprevir and Antiviral Resistancementioning
confidence: 99%